Diseño de un sistema de accionamiento inalámbrico para un extintor para la industria minera (2021)
This degree project proposes the design of a drive system for the containment of heavy machinery fires for the mining sector, which requires less complex and more reliable systems. A modification to the original extinguishing system will be presented; Nitrogen ducts that pressurize dry chemical extinguishers will be reduced, thanks to the detection system and the sprinkling system, which will now be communicated wirelessly by a radio frequency module. As a result, the design drawings of the modified drive mechanism for installation in a mining truck will be obtained.